Radial velocities in the open cluster Trumpler 14 - Levato, Hugo (1991)
In this paper we present radial velocity measurements of probable members of Trumpler 14, a very young open cluster associated with the Carina Nebula. We have found 4 double-line spectroscopic binaries and 2 single-line spectroscopic binaries. We have succeeded in deriving orbital elements for the SB1s. All the binaries are of potential astrophysical interest and are worth further observational efforts.